Relationship between maternal pre-pregnancy BMI and neonatal birth weight in pregnancies with gestational diabetes mellitus: a retrospective cohort study - Liao, Qiuping; Yu, Tiantian; Chen, Jiajia; Zheng, Xiuqiong; Zheng, Lianghui; Yan, Jianying (Frontiers in Medicine, 2025)
AimThe aim of this study was to explore the association between maternal pre-pregnancy body mass index (BMI) and neonatal birth weight in pregnancies with gestational diabetes mellitus (GDM).MethodsThis was a retrospective cohort study conducted between January 2019 and June 2020 at a university hospital in Fuzhou, China.ResultsPre-pregnancy BMI was used to categorize 791 pregnant women as underweight (3.03%), normal weight (51.71%), overweight (32.74%), and obese (12.52%). Among the 791 babies, 11.63% were small for gestational age (SGA), 77.37% were normal weight, and 11.00% were large for gestational age (LGA). The rate of the SGA babies increased with higher pre-pregnancy BMI. The percentage of LGA babies was higher in women who were overweight or obese compared to those of normal weight. Neonatal birth weight displayed a significantly increasing trend with increasing maternal pre-pregnancy BMI when maternal pre-pregnancy BMI was less than 27.78 kg/m2 [β = 0.03, 95% CI (0.01, 0.04); p = 0.0052 < 0.05] when maternal pre-pregnancy BMI was greater than 27.78 kg/m2, neonatal birth weight decreased as maternal pre-pregnancy BMI increased [β = −0.01, 95% CI (−0.04, 0.01); p = 0.3555].ConclusionThe incidence of SGA and LGA babies was higher in the women with GDM who were overweight or obese before pregnancy. The data suggest that different management strategies should be implemented for pregnant women with a pre-pregnancy BMI below 27.78 kg/m2 and above 27.78 kg/m2, particularly in cases of GDM. These findings highlight the importance of providing information, offering preconception counseling, and delivering health education on weight management to ensure healthy pregnancies.